Src kinase associates with a member of a distinct subfamily of protein-tyrosine phosphatases containing an ezrin-like domain. - Møller, N P (1994)
A 6.2-kb full-length clone encoding a distinct protein-tyrosine phosphatase (PTP; EC 3.1.3.48), PTPD1, was isolated from a human skeletal muscle cDNA library. The cDNA encodes a protein of 1174 amino acids with N-terminal sequence homology to the ezrin-band 4.1-merlin-radixin protein family, which also includes the two PTPs H1 and MEG1. The PTP domain is positioned in the extreme C-terminal part of PTPD1, and there is an intervening sequence of about 580 residues without any apparent homology to known proteins separating the ezrin-like and the PTP domains. Thus, PTPD1 and the closely related, partially characterized, PTPD2 belong to the same family as PTPH1 and PTPMEG1, but because of distinct features constitute a different PTP subfamily. Northern blot analyses indicate that PTPD1 and PTPD2 are expressed in a variety of tissues. In transient coexpression experiments PTPD1 was found to be efficiently phosphorylated by and associated with the src kinase pp60src.